Safety of continuing aspirin therapy during spinal surgery: A systematic review and meta-analysis. Issue 46 (November 2017) - Zhang, Chenggui; Wang, Guodong; Liu, Xiaoyang; Li, Yang; Sun, Jianmin
Abstract: Background: Questions whether to continue or discontinue aspirin administration in the perioperative period of spinal surgery has not been systematically evaluated. Objective: The present systematic review is carried out to assess the impact of continuing aspirin administration on the bleeding and cardiovascular events in perispinal surgery period. Methods: Studies were retrieved through MEDLINE, EMBASE, and Springer Link Databases (search terms, aspirin, continue or discontinue, and spinal fusion ), bibliographies of the articles retrieved, and the authors' reference files. We included studies that enrolled patients who underwent spinal surgery who were anticoagulated with aspirin alone and that reported bleeding or cardiovascular events as an outcome. Study quality was assessed using a validated form. 95% confidence interval (95% CI) was pooled to give summary estimates of bleeding and cardiovascular risk. Results: We identified 4 studies assessing bleeding risk associated with aspirin continuation or cardiovascular risk with aspirin discontinuation during spinal surgery. The continuation of aspirin will not increase the risk of blood loss during the spinal surgery (95% CI, −111.72 to −0.59; P  = .05). Also, there was no observed increase in the operative time (95% CI, −33.29 to −3.89; P  = .01) and postoperative blood transfusion (95% CI, 0.00–0.27; P  = .05). But as for the cardiovascular risk without aspirin continuation and mean hospital length of stay with aspirin continuation, we did not get enough samples to make an accurate decision about their relations with aspirin. Conclusion: Patients undergoing spinal surgery with continued aspirin administration do not have an increased risk for bleeding. In addition, there is no observed increase in the operation time and postoperative blood transfusion.